Impact of egg yolk and cysteine on cryopreserved indigenous black rabbit sperm quality in Mekong Delta - Khuong, Tran Thi Thanh; Hoang, Truong Minh; Giang, Tran Thi (Agriculture and Natural Resources, 2024)
Importance of the work: Cryopreservation of indigenous black rabbit sperm poses challenges due to induced damage that affects viability, motility and membrane integrity. Objectives: To evaluate the impact of varying concentrations of cysteine and egg yolk on the cryopreservation medium. Materials & Methods: In Experiment 1, egg yolks were used at concentrations of 0%, 5%, 10% or 15%. In Experiment 2, cysteine was used at concentrations of 0 mM, 1.25 mM, 2.5 mM or 5 mM. Samples were preserved in liquid nitrogen for 72 hours, before being thawed and evaluated. Results: Based on the results in Experiment 1, 15% egg yolk was the optimal concentration for preserving rabbit sperm, with values for overall mobility, progressive motility, viability rate and membrane integrity of 52.31%, 38.74%, 59.32% and 44.79%, respectively. These differences were significant (p < 0.05) compared to the other concentrations. In Experiment 2, the tris citrate glucose (TCG) medium supplemented with 15% egg yolk and combined with 2.5 mM cysteine produced the best results and was significantly (p < 0.05) different from the other concentrations, with overall values for mobility, progressive motility, viability rate and membrane integrity of 63.85%, 45.26%, 74.50% and 51.56%, respectively. Main finding: Using a TCG storage solution enhanced with 15% egg yolk and 2.5 mM cysteine improved rabbit sperm quality during cryopreservation, demonstrating the positive effects of egg yolk and cysteine in sperm cryopreservation.